NUMERICAL AND EXPERIMENTAL EVALUATION OF A LHTES SYSTEM USING PCMS UNDER DIFFERENT CONFIGURATIONS OF NOZZLE AND SHELL INTEGRATED WITH SOLAR EVACUATED TUBE COLLECTORS - Ali Amjed Saeed; Audai Hussein Al-Abbas; Hani Mizhir Magid (Journals Park Publishing, 2025)
To improve the performance of solar energy, this study provides a novel shell and nozzle tube LHTES across two different geometries fins (tilted longitudinal and solid annular) and an investigation of the melting patterns of two types of commercial PCMs (lauric acid and paraffin wax). During the melting (charging) process, numerical simulations were conducted and compared with experimental observations for the bare nozzle pipe and finned tube configurations placed vertically. The average temperature and profile liquid fraction of the PCM through the melting operation in all model setups are employed for validation tests. The evaluation of the liquid fraction revealed that the numerical findings exhibited remarkable qualitative concordance with the experiment in all analyzed cases. The results demonstrate that annular fins and tilted longitudinal designs are seen to enhance the melting rate and temperature distribution by developing heat transfer, which shows an important benefit with an approximate decrease in total melting times of 38.3% and 12.98%. Moreover, three various inlet HTF temperatures (70 °C, 75 °C, and 80 °C) and flow rates (3, 5, and 7 L/min) of the HTF were evaluated during the melting process in PCM. A 5°C rise in the HTF temperature significantly impacted all cases; however, an especially affected reference case enhanced the overall melting time by about 34.97% and 21.32%. The largest decrease in total melting time was around 8.5% when the flow rate was raised from 3 to 7 L/Min. Therefore, the role of the HTF flow rate is less prominent; it can be considered marginal.
Keywords: Latent heat thermal energy storage (LHTES), Phase change material (paraffin wax and lauric acid), Tube shapes, Layout fins, melt fraction, and Heat transfer fluid (HTF).